KENDALA PELAKSANAAN PENDIDIKAN AGAMA ISLAM DI SEKOLAH DASAR NEGERI LOBUGOTI KECAMATAN PANGARIBUAN KABUPATEN TAPANULI UTARA - Tambunan, Nurhalima (Jurnal Ilmiah Al-Hadi, 2017)
This study wasconductedtofindoutthe obstacles of implementation of Islamic education at the Elementary School of Lobugoti Sigotom Julu District Pangaribuan District North Tapanuli. North Tapanuli is a very familiar area with kinship or kinship. It is very unfortunate if this does not care about each other. This research is expected to provide solutions for the implementation of Islamic religious education in the form of procurement of Islamic religious teachers and the provision of school facilities and infrastructure that support the teaching and learning process at the school. Islamic religious education is essentially an effort to transfer religious values, knowledge and culture that are carried out continuously so that values can be a source of motivation and aspirations and benchmarks in the actions and attitudes and thinking patternsfor adherents. Research on the obstacles of the implementation of Islamic religious education in Lobugoti Sigotom Julu State Elementary School, Pangaribuan Tapanuli Utara District is included in field research, withgrounded theory method. Technique of taking informant in this research done by purposive. Data sources are obtained directly through the parties concerned through interviews, observation and document analysis. This research is very useful for the benefit of the people, the nation and the state in realizing the ideals of the Indonesian republic's struggle, where with religious education, the moral of the students become better.